2015
DOI: 10.1007/s00359-015-1043-2
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-wavelength-sensitive opsins are involved in photoreception both in the retina and throughout the central nervous system of crayfish

Abstract: Crayfish have two classes of photoreceptors in the retinas of their reflecting superposition eyes. Long-wavelength-sensitive photoreceptors, comprised of microvilli from R1-7 cells, make up the main rhabdoms. Eighth retinular cells, located distal to the main rhabdoms, house short-wavelength-sensitive photoreceptors. While the opsin involved in long-wavelength sensitivity has long been known, we present the first description of the short-wavelength-sensitive opsin in the retina of the red swamp crayfish, Proca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 14 publications
5
30
1
Order By: Relevance
“…This study provides robust data to demonstrate the different responses in the CPR neurons located in the left and right side of the last ganglion of an isolated nerve cord including the intensities of light, colors of light, and temperature, by extracellular recordings of action potentials. Our results support the presence of the SWS, and the LWS opsins in the CPRs, which showed sensitivities to blue and green light, respectively [20,21]. In addition, the current results provide support for the functional asymmetries described recently as a novel property for both CPR-L and -R when comparing their responses induced by white light pulses in the same species of crayfish C. quadricarinatus [34].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study provides robust data to demonstrate the different responses in the CPR neurons located in the left and right side of the last ganglion of an isolated nerve cord including the intensities of light, colors of light, and temperature, by extracellular recordings of action potentials. Our results support the presence of the SWS, and the LWS opsins in the CPRs, which showed sensitivities to blue and green light, respectively [20,21]. In addition, the current results provide support for the functional asymmetries described recently as a novel property for both CPR-L and -R when comparing their responses induced by white light pulses in the same species of crayfish C. quadricarinatus [34].…”
Section: Discussionsupporting
confidence: 88%
“…Other results have illustrated light-induced activity from the CPR by using a cold white light lamp (light emitting diode), which emitted light with two peaks: blue (446 nm) and green (557 nm) [19]. Kingston and Cronin [20] identified two visual opsin proteins in the crayfish P. clarkii. The short-wavelength-sensitive (SWS) opsin from blue light (440 nm), and the long-wavelength-sensitive (LWS) opsin from green light (530 nm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xenopus tadpoles (Currie et al, 2016), and invertebrates such as insects (Hariyama, 2000), and crustaceans decapods (Simon and Edwards, 1990;Bobkova et al, 2003;Kingston and Cronin, 2015) and the amphipod Talitrus (Frelon-Raimond et al, 2005). The present study also demonstrated that short-wavelength light is preferentially used by the non-ocular photosensory system (Figs 2,3 and 6).…”
Section: ) Andsupporting
confidence: 73%
“…The crayfish Procambarus clarkii has a well-characterized extraocular photoreceptor, called the caudal photoreceptor, located in the sixth abdominal ganglion. SWS and LWS opsin transcripts have been observed not only in the sixth abdominal ganglion, but also in all ganglia of the nerve cord (Kingston and Cronin, 2015). The functional role of the caudal photoreceptor is extended to the triggering of the tail reflex, and to the walking behaviour of the animal.…”
Section: Discussionmentioning
confidence: 97%